Redefinisi Kerugian BUMN dan Implikasinya dalam Putusan Mahkamah Agung No.121 K/PID.SUS/2020 - Wawan Zulmawan; Kathleen Joan Halim; Lathifah Lathifah; Nasya Nadhira; Sandrina Realita; Tyazza Amaranila Ghifari; TheresiaAurellia Gunawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to analyze the relevance of the use of Constitutional Court Decision Number 01/PHPU-Pres/XVII/2019 in the legal considerations of judges in the Supreme Court Decision Number 121 K/Pid.Sus/2020, as well as to examine the authority of directors in making investment decisions in State-Owned Enterprises (BUMN). This research uses a normative legal method with statutory, case, and conceptual approaches. The results show that the Constitutional Court Decision is dominantly used as an initial basis in determining elements of state financial losses, thus forming a legal reasoning construction that tends to be formalistic, focusing on the principle of separate legal entity. This approach has implications for the suboptimal examination of aspects of good faith, due care, and potential abuse of authority in the actions of directors, and causes the application of the business judgment rule doctrine not to be carried out strictly. In addition, this approach has the potential to ignore the concept of beneficial ownership and opens up space for weakening accountability in the management of BUMN. Therefore, a balance is needed between protection of business discretion and enforcement of legal accountability to maintain consistency and legal certainty.